Populations Collapses in Marine Invertebrates Due to Endocrine Disruption: A Cause for Concern? - Fernandez, Marcos Antonio (Frontiers in Endocrinology, 2019)
In the beginning of the XXI century, the International Program on Chemical Safety published a document entitled Global Assessment of the State-Of-The-Science of Endocrine Disruptors. The work indicated only weak evidence of endocrine-related effects in human populations, and in wild animal populations. This document was revised in 2012 (State of the Science of Endocrine Disrupting Chemicals – 2012 (WHO-UNEP, 2012). The new document and the extensive scientific evidence it provided showed clearly that ED effects could be a risk to human and wildlife health. These works, however, were focused in human health and related animal models, mainly vertebrates, and particularly mammals. It can be argued that invertebrates and many other taxa are important parts of all ecosystems, and, in many instances, have been shown to be also vulnerable to endocrine disruption. Thus, this work is aimed to show some important observations on important marine invertebrate taxa, from an ecological point of view. The most important example of endocrine disruption in marine wild populations is the imposex response of marine gastropods, known for more than forty years, and worldwide used to evaluate marine antifouling pollution. Among the mollusks, other important natural resources are the bivalve species used as human food since ancient times and the cephalopods, free-living, highly specialized mollusks, and also important food sources. Some species also showed effects derived from endocrine disruptors, and, what is more serious could bring these compounds to human populations in an almost direct way, sometimes without any form of cooking or preparation. While discussing these questions, this work is also aimed to stimulate research on endocrine disruption among the invertebrate taxa that inhabited our oceans, and on which these effects are poorly known today.